The relationship between online campaigning and political involvement. Issue 5 (12th September 2016) - Kruikemeier, Sanne; van Noort, Guda; Vliegenthart, Rens; H. de Vreese, Claes
Abstract : Purpose: The purpose of this paper is to examine the causal relationship between interactive and personal campaigning on social media and political involvement, and the mechanisms that explain the effects. Specifically, this study examines whether personal and interactive communication on Twitter increases political involvement among citizens through social presence and perceived expertise. Design/methodology/approach: An experimental design – a 2 (low vs high interactivity)×3 (depersonalized vs individualized vs privatized communication) between-subjects design – is used. Findings: The findings show that interactive communication leads to a stronger sense of social presence and source expertise, which positively affect involvement. The effects of personal campaigning differ. Individualized communication positively affects involvement via source expertise. Interestingly, privatized communication positively affects involvement via social presence, but negatively via source expertise. Originality/value: Although a growing body of work examines the political consequences of social media, there is still very little understanding why social media affect citizens. The current study fills this void by investigating how the use of social media affects political involvement among citizens.